Spermatotoxicity and Testicular Pathology in Wistar Strain Rats fed Graded Levels of Pigeon Pea Diet (Nigerian Journal of Physiological Sciences, 2021)
Summary: Pigeon pea is an important grain legume in the tropics and subtropics and it is a valuable source of low-cost plant protein for humans and animals, but it remains an underutilized legume. Effects of feeding graded levels of raw pigeon pea seed inclusion diets on testicular function in Wistar rats was investigated. Thirty male Wistar rats weighing between 120 and 160 g were assigned into six groups (A-F) of 5 rats each. Group A rats served as the control and were fed with standard rat feed, Group B was fed with 10% pigeon pea inclusion diet, group C: 20% pigeon pea inclusion diet, Group D: 30% pigeon pea inclusion diet, Group E: 40% pigeon pea inclusion diet and Group F: 100% pigeon pea diet. Each rat received 30 g of feeds per day for 21 days with drinking water ad libitum. All analyses were carried out using standard methods. The motility scores were between 34.00±2.45 and 87.00±3.00 with the control group A having the significantly highest score (P